Book and Library: A Life with Books, A Gift to Mustafa Vedat SÖNMEZ - Aydemir Şenay, Burcu (Information World, 2023)
There are 27 articles under four different sections: “Historical Libraries”, “Republican Period Libraries”, “World Libraries” and “Books in Turks Throughout History”, including an article including Mustafa Vedat SÖNMEZ’s interview, and an evaluation of libraries over different periods, as well as history. The work titled “Book and Library: A Life with Books, A Gift to Mustafa Vedat SÖNMEZ”, in which the book and book culture among Turks was discussed throughout the period, was prepared by evaluating it as an introductory article.
Keywords: Historical libraries; World libraries; Republican Era libraries; Books in Turks; Book and library